Peran Sistem Pemerintah Berbasis Elektronik (SPBE) Dalam Meningkatkan Aksesibilitas Pelayanan Publik di Indonesia - Laili Choirunnisa; Try Hajar Caesar Oktaviana; Ahmad Ainur Ridlo; Elva Imeldatur Rohmah (Sosio Yustisia: Jurnal Hukum dan Perubahan Sosial, 2023)
Efficient and accessible public services are an essential aspect of the development of a country. In Indonesia, as a country with a large and diverse population and a large area, the challenge of providing equitable accessibility of public services for all people is complex. However, with the rapid advancement of information and communication technology, electronic-based government systems have emerged as a potential solution to improve the accessibility of public services in Indonesia. This study aims to analyze the role of electronic-based government systems in improving the accessibility of public services in Indonesia and the resulting benefits. This research uses an analytical descriptive approach by collecting data through literature study and analysis of related documents. The results show that the electronic-based government system is vital in improving the accessibility of public services in Indonesia. By reducing physical barriers, increasing efficiency, and providing co-benefits such as transparency and more active public participation, these systems can speed up public service processes and increase community satisfaction. To optimize the role of electronic-based government systems, joint efforts between the government, the private sector, and the public need to be made to improve infrastructure, digital literacy, and data protection.